RESPON BIBIT KELAPA SAWIT ATAS PEMBERIAN PUPUK ORGANIK PADA TANAH GAMBUT DI KALIMANTAN TENGAH (Palm oil seedling response of organic fertilizer on peat soil in Central Kalimantan) - ., Sustiyah; Y, Sulistiyanto; Z, Damanik, (AGRIPEAT, 2018)
ABSTRACTThe purpose of this study was to determine response  of main nursery palm seedlings for application of organic fertilizers on soil peat. The experiment used completely randomized factorial design consisting of two factors. The first factor was petroganik fertilizers (P)  consists of four levels: Po = control or no petroganik (0 kg/plants), P1 = petroganik 0,5 kg/plants, P2 = Petrogenik 1 kg/plants;  P3 = Petrogenik 2 kg/plans. The second factor was bokhasi kayambang fertilizers (K) consists of four levels: Ko = control or no bokhasi kayambang (0 kg/plants); K1 = Bokhasi Kayambang 0,5 kg/plants; K2 = Bokhasi Kayambang 1 kg/plants; K3 = Bokhasi Kayambang 2 kg/plants. The each treatment was replicated five times. Observed variables were plant height, number of leaf midrib, number of primary root and length of primary root. Results showed that interaction between the application of petroganik fertilizers 2 kg/plants and bokhasi kayambang fertilizers 1 kg/plants (P3K2), respond positively to the growth of oil palm seedlings main nursery whith soil pH 5,95.  This treatment produced the highest plant height, the largest number of leaf midrib, the best root number and length of primary root.Key word : oil palm seedling, rubber waste liquid, fertilizer